Angiotensin receptor blockers = angiotensin converting enzyme inhibitors minus dry cough? - Kamath, Ashwin (International Journal of Basic & Clinical Pharmacology, 2017)
Blockade of the renin angiotensin aldosterone system (RAAS) is an important pharmacological intervention in cardiovascular (CV) diseases. Hypertension, heart failure (HF) and myocardial infarction are important indications for use of angiotensin converting enzyme inhibitors (ACEIs), which potentially decrease morbidity and prolong survival. Dry cough is an important adverse effect seen in about 20% of the patients which might require discontinuation of the drug. In such situations, angiotensin receptor blockers (ARBs) serve as replacement drugs in all the indications, as they are largely devoid of this limiting adverse effect.